The Effectiveness of an Ethno Project-Based Teaching Module Integrated with Technology in Basic Culinary Learning to Improve Vocational High School Students’ Learning Interest - I Gusti Ayu Agung Sinta Diarini; Ida Bagus Neo Kurnia Amadea; IGusti Ayu Ika Monika Prasthayandari (Jurnal Pedagogi dan Pembelajaran, 2026)
Learning in culinary vocational education at vocational high schools is still predominantly characterized by conventional teacher-centered methods, resulting in suboptimal student engagement in the learning process. In addition, the limited use of educational technology and the lack of integration of local culinary cultural contexts contribute to students' low learning interest in Basic Culinary subjects, as indicated by low enthusiasm, participation, and learning independence. This study aimed to analyze the effectiveness of an Ethno Project-Based Teaching Module integrated with technology in improving students' learning interest in Basic Culinary subjects at vocational high schools. The study employed a pre-experimental design with a pretest-posttest control group, involving 33 students divided into two groups: an experimental group that used a technology-integrated ethno-culinary project-based module and a control group that received conventional learning instruction. The results showed a significant improvement in students’ learning interest in the experimental group after the implementation of the module, as indicated by a significant difference between pretest and posttest scores (t = 145.157; sig. = 0.000). The study concluded that the technology-integrated Ethno Project-Based Teaching Module was effective in improving students’ learning interest in Basic Culinary subjects. The findings imply that this module can serve as an innovative learning alternative based on local culture and technology to enhance student engagement in vocational education.